Evaluating the Use of TiO2 Nanoparticles for Toxicity Testing in Pulmonary A549 Cells - Bacova, Jana; Knotek, Petr; Kopecka, Katerina; Hromadko, Ludek; Capek, Jan; Nyvltova, Pavlina; Bruckova, Lenka; Schröterova, Ladislava; Sestakova, Blanka; Palarcik, Jiri; Motola, Martin; Cizkova, Dana; et al. (International journal of nanomedicine, 2022)
PURPOSE: Titanium dioxide nanoparticles, 25 nm in size of crystallites (TiO2 P25), are among the most produced nanomaterials worldwide. The broad use of TiO2 P25 in material science has implied a request to evaluate their biological effects, especially in the lungs. Hence, the pulmonary A549 cell line has been used to estimate the effects of TiO2 P25. However, the reports have provided dissimilar results on caused toxicity. Surprisingly, the physicochemical factors influencing TiO2 P25 action in biological models have not been evaluated in most reports. Thus, the objective of the present study is to characterize the preparation of TiO2 P25 for biological testing in A549 cells and to evaluate their biological effects. METHODS: We determined the size and crystallinity of TiO2 P25. We used four techniques for TiO2 P25 dispersion. We estimated the colloid stability of TiO2 P25 in distilled water, isotonic NaCl solution, and cell culture medium. We applied the optimal dispersion conditions for testing the biological effects of TiO2 P25 (0-100 µg.mL-1) in A549 cells using biochemical assays (dehydrogenase activity, glutathione levels) and microscopy. RESULTS: We found that the use of fetal bovine serum in culture medium is essential to maintain sufficient colloid stability of dispersed TiO2 P25. Under these conditions, TiO2 P25 were unable to induce a significant impairment of A549 cells according to the results of biochemical and microscopy evaluations. When the defined parameters for the use of TiO2 P25 in A549 cells were met, similar results on the biological effects of TiO2 P25 were obtained in two independent cell laboratories. CONCLUSION: We optimized the experimental conditions of TiO2 P25 preparation for toxicity testing in A549 cells. The results presented here on TiO2 P25-induced cellular effects are reproducible. Therefore, our results can be helpful for other researchers using TiO2 P25 as a reference material.
Keywords: Nanoparticles; dispersion; Humans; nanoparticles; P25; chlorid sodný; A549 Cells; Lung; lidé; kovové nanočástice; plíce; titan; Glutathione; oxidoreduktasy; titanium dioxide; Titanium; voda; nanočástice; sérový albumin hovězí; glutathion; Serum Albumin, Bovine; Water; Sodium Chloride; nanotoxicity; buňky A549; Oxidoreductases; Metal Nanoparticles; A549 cells